Fome de Cidadania e o Direito à Alimentação: a percepção dos usuáios do Restaurante Popular Mesa do Povo em Fortaleza-CE - Dutra, Márcia Maria de Medeiros (2007)
The eradication of hunger and the promotion of Food and Nutritional Security (SAN) are central themes from national policy agenda at present time and in order to achieve this level of priority is a result of a long errand. The Brazilian experience has advanced by strides and has been consolidating on a perspective of building from SAN’s public intersectorial policy and from insertion of Human rights’ approach to an adequate food (DHAA) on the other sectorial policies. Many enterprises are been implemented with different focuses, including the Popular Restaurants’ plan, which its objective is to amplify the access from the vulnerable populations to an adequate food. In spite of the improvements, the population is far from getting their right to food accomplished. The rights’ approach can help with the improvement of the State’s performance, since its introduction until SAN’s actions improvement. Therefore, this investigation proposes to understand the perceptions of “Mesa do Povo” popular restaurant users, located in Fortaleza, in relation to their rights, on a general perspective about citizenship and food as a right. In that clipping, it pretends to understand what measurement the contents from the discussions about SAN’s issues and the food rights, broken out over the last decades, are being appropriated by the public from an act of food security. In that trajectory it was configured the users’ profile and recovered the social-historical process of citizenship and the SAN’s construction. The adopted methodology included bibliographic, documentary and field research, using a qualitative approach through the discussion in focal groups. The findings from this research let clear the magnitude of the gap between the real and the legal situation. It shows the emergency of promoting an education for citizenship and brings up conditions for the population’s empowerment about SAN and DHAA’s issues and, consequently, for the development of an active citizenship in which the community can mobilize itself and claim to have the right to an adequate food.